50.1k views
5 votes
Rewrite the given rational expression in the form q(x) + r(x)/b(x) where q(x) = quotient, r(x) = remainder, and b(x) = divisor.(x3 – x – 23)/(x + 1)- x2 –x(x2 – x)– 23/(x + 1)x2+ x(-x2 + x)– 23/(x + 1)

Rewrite the given rational expression in the form q(x) + r(x)/b(x) where q(x) = quotient-example-1
User Chrisis
by
5.1k points

1 Answer

3 votes

Given


(x^3+2x^2+3x+2)/(x+1)

To rewrite the expression using synthetic division.

Step-by-step explanation:

It is given that,


(x^3+2x^2+3x+2)/(x+1)

That implies,

Set x + 1 = 0.

Then, x = -1.

Therefore, by using synthetic division,

Hence, the expression is rewritten as,


x^2+x+2

Rewrite the given rational expression in the form q(x) + r(x)/b(x) where q(x) = quotient-example-1
User Kirill Reva
by
4.6k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.